Durability of vapor-permeable waterproof textile materials used in sailing protective apparel. Issue 24 (December 2018) - Troynikov, Olga; Nawaz, Nazia; Watson, Chris
Vapor-permeable waterproof textiles (VPWTs) are used in sailing apparel to protect wearers from weather and water exposure. They must also withstand knocks and abrasion. Failure of fabric waterproofing results in water intrusion, reduced thermal protection and potentially hypothermia. There are no standard methods for testing the waterproof durability of fabrics in these conditions. To evaluate waterproofing durability, we simulated high levels of wear on leading commercially available VPWT assemblies through mechanical treatment in wet conditions. To compare fabrics on multiple performance characteristics, we developed a Total Durability Penalty index associated with leaks and ruptures, weighted by failure pressure. The experiment revealed significant differences in VPWT deterioration under mechanical treatment. We determined that the mass per unit area and thickness of VPWT fabrics are positively correlated with pressure at leakage; that rupture is significantly and negatively associated with the mass per unit area and thickness of the inner and outer layers of fabric; and leakage pressure is positively correlated with the same parameters. These results show that it is important to consider wear conditions when assessing the long-term performance attributes of protective clothing assemblies.